[Wage ; 14 K ; Divisoria Mafia [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Looks into the real wages of working people their buying power and determination. Fourteen musically gifted children under the guidance of Ryan Cayabyab are the feature artists in this piece about their talent and their own dreams. Takes a look into the Divisoria mafia that manipulates the prices of good coming through Divisoria.